Cellular Technologies in Traumatology: From Cells to Tissue Engineering - N. N. Dremina (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
Injuries and degenerative changes of tendons are common damages of the musculoskeletal system. Due to its hypovascular character the tendon has a limited natural ability to recover. For typical surgical treatment, the tendon integrity is restored, but in most cases, there occurs formation of the connective tissue scar resulting in structural and mechanical functionality disruption. The insufficient effectiveness of traditional therapy methods requires the search for alternative ways to restore damaged tendon tissues. This article discusses new effective methods for improving the treatment that base on the use of cellular technologies among which one of the main directions is mesenchymal stem cell application. Due to mesenchymal stem cells, there is a shift from pro-fibrotic and pro-inflammatory reactions of cells to pro-regenerative ones. Stem cells being multipotent and having among other things tenogenic potential are considered a promising material for repairing damaged tendons. The article also describes the sources of progenitor tendon cells including the tendon bundles and pericytes the main markers of which are Scx and Mkx that are proteins of the transcription factor superfamily, and Tnmd that is transmembrane glycoprotein.The growth factors that not only enhance the proliferative activity of mesenchymal stem cells but also promote in vitro tenogenic genes expression as well as the collagen Itype production what is necessary for tendon formation are considered. Along with growth factors, the morphogenetic protein BMP14 is presented, this protein increases themesenchymal stem cell proliferation and contributes directed tenogenic differentiation of these cells, suppressing their adipogenic and chondrogenic potentials.In recent years, mesenchymal stem cells have been used both separately and in combination with various growth factors and different three-dimensional structures providing the interaction with all of the cell types.The issues of the latest 3D-bioprinting technology allowing to make tissue-like structures for replacement damaged tissues and organs are discussed. 3D-bioprinting technology is known to allow acting exact spatio-temporal control of the distribution of cells, growth factors, small molecules, drugs and biologically active substances.